1983
DOI: 10.1210/jcem-56-1-181
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Dopamine Receptors in the Naloxone-Induced Hormonal Changes in Man

Abstract: To assess the role of dopamine receptors in naloxone-induced hormonal changes, the effects of dopamine and metoclopramide on anterior pituitary hormone secretion were studied during the infusion of the opiate blocker in normal men. Naloxone stimulated LH and cortisol secretion in all subjects, whereas FSH, TSH, PRL, and GH did not change. The infusion of dopamine completely suppressed the naloxone-induced LH rise; on the contrary, metoclopramide failed to alter the magnitude of the increments in LH observed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…High doses of fenfluramine may also block dopaminergic receptors (Jori & Bernardi, 1972;Fuller ef al., 1976); however the dose used in this study, as indicated by previous experiments, probably did not block dopaminergic receptors (Quattrone et a/.. 1978;Ferrari et al, 1980;Foresta et al, 1985b). Moreover, we have recently demonstrated (Foresta et al, 1985a), as first suggested by Delitala et al (1983). that in man drugs with specific antidopaminergic effects, such as sulpiride and metoclopramide, did not influence the naloxone-induced LH increase.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…High doses of fenfluramine may also block dopaminergic receptors (Jori & Bernardi, 1972;Fuller ef al., 1976); however the dose used in this study, as indicated by previous experiments, probably did not block dopaminergic receptors (Quattrone et a/.. 1978;Ferrari et al, 1980;Foresta et al, 1985b). Moreover, we have recently demonstrated (Foresta et al, 1985a), as first suggested by Delitala et al (1983). that in man drugs with specific antidopaminergic effects, such as sulpiride and metoclopramide, did not influence the naloxone-induced LH increase.…”
Section: Discussionsupporting
confidence: 52%
“…Metergoline pretreatment significantly enhanced the stimulatory effects of naloxone on LH secretion. It has been suggested that metergoline may act also as a dopaminergic agent, however in man it has been demonstrated that dopaminergic drugs block the stimulatory effects of naloxone on LH secretion (Delitala et al, 1983;Foresta el al., 1985b). Therefore the hypothesis that opioid peptides influence LH secretion through the involvement of the serotoninergic system is further supported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly and probably more importantly, they contradict the findings in man of Morley et al [5] and Delitala el al. [7] who could not find any effect of naloxone at high doses (10 and 20 mg i.v. respectively) on the release of PRL caused by metoclopramide, another selective dopamine receptor antagonist 181.…”
Section: Discussionmentioning
confidence: 93%
“…observa tions] further supports this view. Moreover, Delitala et al [7] reported recently that metoclopramide failed to antago nise the naloxone-induced rise in plasma LH in normal hu man male subjects, suggesting a direct rather than dopa mine-mediated suppressive action of opioid peptides on GnRH release.…”
Section: Discussionmentioning
confidence: 99%